Higher Education Markets, Theory and Practice (Journal of Education and Development, 2018)
Curtis Jr (2018) restates theories Individual Leisure Theory, with Price-Adjustments, for Individuals in Capital Markets, and Individual Returns to Accumulation vs. Latent Systems, with considerations of Expected Returns, Information & Market Clearing and how Graduate Program degree candidates and universities can increase higher education market efficiency with effective form administration through enhancing i. admissions administration, ii. degree administration, iii. employment administration, and iv. publishing administration.